Reforma a vapor do etanol sobre catalisadores de Ni e Co suportados - Liberatori, Janete Werle de Camargo (Universidade Federal de São Carlos, 2004)
The Ni and Co catalysts supported on Al2O3 and 12%La-Al2O3 and the carrier 12%La-Al2O3 were prepared by impregnation of the support with an aqueous solution of corresponding nitrates metals. The catalysts were characterized by temperature programmed reduction (TPR), specific surface area (B.E.T.) and XRay Diffraction (XRD). The reaction rate for decomposition of ethanol in homogeneous phase becomes significant relative to the heterogeneous reaction at higher temperature (≥ 620ºC). The Ni/Al2O3 catalyst with higher Ni loading (15 wt.%) is active for dehydrogenation and hydrogenolysis of ethanol at temperatures lower than 500ºC, showing high selectivity to CH4 and CO. The rate to steam reforming of CH4 over Ni/Al2O3 catalyst became significant at temperature higher than 500ºC. The Co/Al2O3 catalyst with high Co loading (12 wt %) is mainly active for dehydrogenation at temperatures lower than 480ºC, showing high selectivity to steam reforming of ethanol, forming predominantly CO2. The selectivity to CH4 was suppressed on La-containing catalysts (Ni/La-Al2O3 and Co/La-Al2O3). The decreasing Co loading from 12 to 1 wt % in the Co/La-Al2O3 catalyst provides a decreasing on the selectivity to dehydrogenization of ethanol. The La-Al2O3 support shows active sites for dehydrogenation of ethanol, these sites are blocked increasing the Co loading. The Ni and Co catalysts show activity for carbon deposition. The addition of the promoters Ag and Sn have no positive effect to suppress the carbon deposition. The carbon deposition was suppressed increasing water/ethanol ratio up to stoichiometric ratio.
Keywords: Catálise; Reforma a vapor; Álcool; Níquel; Cobalto; ENGENHARIAS::ENGENHARIA QUIMICA